Pengembangan Bahan Ajar Lembar Kerja Peserta Didik dengan Pendekatan Saintifik pada Materi Gaya untuk Siswa Kelas IV - Leni Hestina; Irwan Koto; Endang Widi Winarni (UNIB Press, 2023)
The purpose of this study was to develop learning materials for students' worksheets with a scientific approach to material force for fourth grade students. The research subjects were 22 students and one grade IV teacher at SDN 59 Bengkulu Tengah, while the research object was students' worksheets with a scientific approach. This study uses the ADDIE model development which is carried out to produce a learning product. These stages include analysis, design, development, implementation, and evaluation. However, the development carried out is only up to the third stage (development). The instruments used were expert validation sheets, interview guides and practicality test questionnaires. The results showed that the learning materials for students' worksheets with the scientific approach developed were very feasible and practical to be used by fourth grade students and teachers in science learning, especially force material, muscle force sub material.